Metabolic profiling and environmental characterisation of salterns in the islands of Cabo Verde. Issue Volume 1(2019)Issue A (8th March 2019) - McCulloch, Bryn; Rowson, James; da Mour, Aires; Rocha, Hélio; Filipa Simões, Marta; Antunes, André
Abstract : The Cabo Verde Islands constitute a biodiversity hotspot, encompassing a wide range of different biotopes. Thus far, most surveys and programmes have focused exclusively on the flora and/or fauna of the islands and no effort has been made to systematically assess and preserve locally existing microbial biodiversity. The absence of such studies is especially troubling regarding their traditional salterns, as many of them have been abandoned, and increase of construction in coastal areas has already started to indelibly change some of these unique ecosystems and will likely obliterate some of them. Here we provide an overview of the preliminary data recently collected from salterns in the islands of Sal, Maio, and Boavista and include details on their previously unreported physical-chemical characteristics (salinity, pH, temperature and ionic composition), as well as first results on microbial metabolic profiling. Our data has shown a wide diversity of environmental niches (particularly noticeable in Maio), and showcased differences in substrate use both between and within different salterns. These are the first step of our ongoing efforts in assisting in the survey of several threatened extreme environments in Cabo Verde, characterising their geochemistry and microbiology, and identifying their potential biotechnological applications.